Metal organic network glassy material and preparation method thereof

By using transition metal inorganic salts and amide compounds in metal organic network glass materials, combining the synergistic effects of amide ligands and anionic ligands, metal organic network glass materials with lower melting points are prepared, which solves the problem of thermal decomposition and cold crystallization during the preparation process and achieves the improvement of the thermal stability of the material.

CN119570047APending Publication Date: 2025-03-07SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410160278.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-02
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing metal organic network glass materials are prone to thermal decomposition during the preparation process, and cold crystals are prone to occur during the heat treatment process, resulting in insufficient thermal stability.

Method used

By using transition metal inorganic salts and amide compounds, combining the synergistic effects of amide ligands and anionic ligands, coordination units with elongated octahedral were synthesized, and hydrogen bonds and weak electrostatic interactions between cations and anions were introduced between these coordination units to prepare metal organic network glass materials with lower melting points.

Benefits of technology

The melting point of the material is reduced to only about 100°C, and the glass formation ability is enhanced through coordination and hydrogen bond synergistic effects, avoiding cold crystallization and improving the thermal stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570047A_ABST
    Figure CN119570047A_ABST
Patent Text Reader

Abstract

The invention relates to a metal organic network glassy material and a preparation method thereof, and belongs to the technical field of metal organic network glassy materials. The metal organic network glassy state material comprises transition metal inorganic salt and an amide compound, and the amide compound is used as a ligand; the molar ratio of the transition metal inorganic salt to the amide compound is (3-6): 1. According to the present invention, by using the synergistic effect of the amide ligand and the anion ligand, the elongated octahedral coordination units are synthesized, and the hydrogen bonds and the weak electrostatic interaction between the spatially separated cations and anions are introduced between the coordination units, such that the material has the low melting point; meanwhile, a short-range ordered and long-range disordered glassy structure is formed, so that the material can be applied to the fields of optical materials, energy storage materials and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of metal organic network glassy materials, and in particular to a metal organic network glassy material and a preparation method thereof. Background Art

[0002] Metal-organic network glassy materials are a type of amorphous structure inspired by the design of coordination polymers and metal-organic frameworks. They are glassy materials formed by metal cations and organic bridging ligands, prepared using coordination chemistry and network design principles. Metal-organic network glassy materials can improve their long-range structural correlation by tailoring the network topology and regulating the length of organic bridging ligands, thereby changing their material properties. This property is unattainable by traditional inorganic, organic and metallic glasses. In addition, the glassy bodies formed by metal-organic networks have the properties of plasticity and no grain boundaries, which makes it possible to prepare homogeneous membranes for gas separation, defect-free solid electrolytes, special optical materials, and hybrid composite energy storage materials.

[0003] At present, there are two main methods for synthesizing metal organic network to form glass, namely melt quenching method and mechanical induction method. The melt quenching method is to heat the synthesized metal organic framework crystal to liquid state, and then transform it into glassy material by rapid cooling. This method is limited by the fact that the thermal degradation temperature of most crystalline materials for preparing glassy state is lower than their melting point, so the material usually undergoes thermal decomposition before melting, which poses a great challenge to its thermal stability. The mechanical induction method is a process of directly converting crystals into glassy state through compression, shear and tensile stress. Compared with the high-energy melting process of the melt quenching method, the mechanical induction method is a relatively green method. As an alternative to the non-melting preparation method, the most common treatment method of the mechanical induction method is to induce the direct conversion of crystals into glassy state through ball milling. However, the glassy material prepared by the mechanical induction method is prone to residual nuclei, which induces cold crystallization. Therefore, during the heat treatment process exceeding the cold crystallization temperature, these residual nuclei will continue to grow, causing the amorphous material to crystallize again. If you want to convert the recrystallized material back into glassy state, you must heat it to the melting point and then cool it. Therefore, in application scenarios that require temperature cycling, glassy materials prepared using the mechanical induction method actually need to be treated similarly to the melt quenching method, which also brings challenges in terms of its thermal stability. So far, research on the preparation of metal organic network glassy materials has mainly focused on increasing the decomposition temperature, which is achieved by using high thermal stability ligands. At the same time, there is relatively little research on designing metal organic network glassy materials with inherently lower melting points. Summary of the invention

[0004] In view of the deficiencies in the prior art, the purpose of the embodiments of the present application includes providing a metal organic network glassy material and a preparation method thereof, so as to improve the technical problems of the existing metal organic network glassy materials being easily thermally decomposed during the preparation process and easily cold crystallized during the heat treatment process.

[0005] In a first aspect, an embodiment of the present application provides a metal organic network glassy material, comprising a transition metal inorganic salt and an amide compound, wherein the amide compound serves as a ligand; the molar ratio of the transition metal inorganic salt to the amide compound is (3-6):1.

[0006] This application synthesizes elongated octahedral coordination units by using the synergistic effect of amide ligands and anionic ligands, and introduces hydrogen bonds and weak electrostatic interactions between spatially separated cations and anions between these coordination units, so that the obtained metal organic network glassy material has a lower melting point than other metal organic network glassy materials, which is only about 100°C. The main reason for this property is that charge delocalization and spatial separation of anions and cations reduce the electrostatic attraction between charges, as well as the synergistic effect of strong and weak ligands and weak hydrogen bond interactions. At the same time, a short-range ordered and long-range disordered glassy structure is formed, which gives the material a series of physical and chemical properties, allowing it to be used in optical materials and energy storage materials.

[0007] Within the molar ratio range of (3-6):1, the reaction rate, structural stability and product properties can be better balanced, thereby obtaining a more ideal metal organic network glassy material.

[0008] In some embodiments of the present application, the cation in the transition metal inorganic salt includes Mn 2+ , Fe 2+ 、Co 2+ 、Ni 2+ , Cu 2+ and Zn 2+ At least one of; the anion in the transition metal inorganic salt includes Cl - 、NO3 - and SO4 2- At least one of .

[0009] By pairing the above-mentioned transition metal cations and anions, the diversity and adjustability of metal organic networks can be achieved, and a more stable coordination structure can be formed to enhance the stability of metal organic networks. Different combinations of transition metal ions and anions will lead to different chemical and physical properties, thereby meeting the needs of different application fields. In addition, the selection of the above-mentioned transition metal ions can introduce different electronic structures and magnetic properties into the metal organic network, thereby optimizing its electronic conductivity, magnetic properties or other specific properties. This helps to customize the properties of the metal organic network to suit different uses.

[0010] In some embodiments of the present application, the amide compound includes at least one of acetamide, isobutylamide, oxalyl diamine, N,N-dimethylformamide, dimethylacetamide, succinamide, carbonamide, N-methylurea and 1,3-bis(hydroxymethyl)urea. By selecting the above different types of amide compounds, the structure, properties and reaction conditions of the metal organic network can be regulated to meet the needs of different application fields for metal organic network materials.

[0011] In some embodiments of the present application, the transition metal inorganic salt is anhydrous manganese chloride, and the amide compound is methyl urea; or, the transition metal inorganic salt is anhydrous cobalt chloride, and the amide compound is methyl urea; or, the transition metal inorganic salt is anhydrous nickel chloride, and the amide compound is methyl urea.

[0012] Inorganic salts such as anhydrous manganese chloride, anhydrous cobalt chloride or anhydrous nickel chloride are selected because their metal cations have good ligand affinity with amide compounds such as methyl urea, which helps to form a stable coordination compound in the reaction.

[0013] In the second aspect, an embodiment of the present application provides a method for preparing the above-mentioned metal organic network glassy material, comprising: mixing a transition metal inorganic salt with a first solvent to obtain a first reaction liquid; mixing an amide compound with a second solvent to obtain a second reaction liquid; mixing the first reaction liquid and the second reaction liquid, stirring and reacting to obtain a mixed solution; solid-liquid separation to obtain a liquid component in the mixed solution, removing the first solvent and the second solvent in the liquid component, to obtain a metal organic network glassy material; the boiling points of the first solvent and the second solvent are lower than the boiling points of the amide compound.

[0014] The solution method of the present application can greatly reduce the temperature required for its preparation, thereby effectively reducing thermal decomposition. Moreover, the metal organic network glassy material prepared by the preparation method provided by the present application has a strong glass-forming ability due to the synergistic effect of its coordination bond and hydrogen bond, thereby avoiding the formation of crystal nuclei during the cooling process, thereby avoiding cold crystallization.

[0015] In some embodiments of the present application, the first solvent and the second solvent are the same or different; the first solvent includes ethanol and / or methanol, and the second solvent includes ethanol and / or methanol.

[0016] In some embodiments of the present application, 20-30 mL of the first solvent is added to every 1 mmol of the transition metal inorganic salt. Adding 20-30 mL of the first solvent to every 1 mmol of the transition metal inorganic salt can fully dissolve the transition metal inorganic salt, so that it can be evenly mixed in the reaction system, which is conducive to the reaction.

[0017] In some embodiments of the present application, 4-6 mL of the second solvent is added to every 1 mmol of the amide compound. Adding 4-6 mL of the second solvent to every 1 mmol of the amide compound can fully dissolve the amide compound, so that it can be evenly mixed in the reaction system, which is conducive to the reaction.

[0018] In some embodiments of the present application, the stirring temperature is 25° C., and the stirring time is 1.5-2.5 h.

[0019] In the third aspect, an embodiment of the present application provides a method for preparing the above-mentioned metal organic network glassy material, comprising: heating an amide compound to obtain a molten amide compound; stirring a transition metal inorganic salt and the molten amide compound to react, and cooling to obtain the metal organic network glassy material; the temperature of the stirring reaction is not lower than the temperature of the molten amide compound, and at the same time not higher than the boiling point or decomposition temperature of the molten amide compound.

[0020] The solution method is suitable for large-scale preparation, but a small amount of solvent molecules will inevitably remain in the preparation process. Preparation by the melt method can make the molecular structure of the product clearer, and there is no interference from solvent molecules, so the prepared sample is more suitable for analyzing the molecular structure. Moreover, the ligand selected in this application has a low melting point, so it can be prepared by the melt method.

[0021] In some embodiments of the present application, the stirring reaction temperature is 105-110° C., and the stirring reaction time is 1.5-2.5 h. Within the above stirring reaction temperature range, the reaction rate can be balanced, which is conducive to the formation of a metal organic network, thereby obtaining an ideal metal organic network glass material. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 This is an extended X-ray absorption fine structure (EXAFS) spectrum of the metal-organic network glassy material in Example 1 of the present application;

[0024] Figure 2 This is an X-ray absorption near edge structure (XANES) spectrum of the metal organic network glassy material in Example 1 of the present application;

[0025] Figure 3The X-ray diffraction (XRD) pattern of the metal organic network glassy material in Example 1 of the present application is compared with the crystal structure of methyl urea and manganese chloride;

[0026] Figure 4 is a differential scanning calorimetry (DSC) curve of the metal organic network glassy material in Example 1 of the present application and the crystalline material formed after being fully ground;

[0027] Figure 5 This is the change in viscosity of the metal organic network glassy material in Example 1 of the present application with temperature. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0029] The present application provides a metal organic network glass material, and the preparation method thereof includes the following two methods:

[0030] Method 1: Solution method

[0031] Step S101. Mix a transition metal inorganic salt and a first solvent to obtain a first reaction solution; and add 20-30 mL of the first solvent to every 1 mmol of the transition metal inorganic salt.

[0032] Among them, the cations in the transition metal inorganic salts include Mn 2+ , Fe 2+ 、Co 2+ 、Ni 2+ , Cu 2+ and Zn 2+ At least one of; the anion in the transition metal inorganic salt includes Cl - 、NO3 - and SO4 2- At least one of. For example, the transition metal inorganic salt can be selected from one or more of manganese chloride, ferrous chloride, cobalt chloride, nickel chloride, cupric chloride, zinc chloride, manganese nitrate, ferrous nitrate, cobalt nitrate, nickel nitrate, cupric nitrate, zinc nitrate, manganese sulfate, ferrous sulfate, cobalt sulfate, nickel sulfate, cupric sulfate and zinc sulfate.

[0033] By pairing the above-mentioned transition metal cations and anions, the diversity and adjustability of metal organic networks can be achieved, and a more stable coordination structure can be formed to enhance the stability of metal organic networks. Different combinations of transition metal ions and anions will lead to different chemical and physical properties, thereby meeting the needs of different application fields. In addition, the selection of the above-mentioned transition metal ions can introduce different electronic structures and magnetic properties into the metal organic network, thereby optimizing its electronic conductivity, magnetic properties or other specific properties. This helps to customize the properties of the metal organic network to suit different uses.

[0034] Step S102. Mix the amide compound with the second solvent to obtain a second reaction solution; and add 4-6 mL of the second solvent to every 1 mmol of the amide compound.

[0035] Among them, the amide compounds include but are not limited to at least one of acetamide, isobutylamide, oxalyl diamide, N,N-dimethylformamide, dimethylacetamide, succinamide, carbonamide, N-methyl urea and 1,3-bis(hydroxymethyl)urea.

[0036] By selecting the above-mentioned different types of amide compounds, the structure, properties and reaction conditions of the metal organic network can be regulated to meet the needs of metal organic network materials in different application fields. For example, by selecting 1,3-bis(hydroxymethyl)urea, a hydrogen-containing ketone group may be introduced, which helps to increase the active hydrogen content in the reaction system and is suitable for reactions such as hydrogen transfer reactions that require the participation of active hydrogen. By selecting carbonamide, a carbonamide group may be introduced, which helps to introduce a carbonamide structure into the metal organic network, thereby increasing the diversity and functionality of the material and is suitable for the design of metal organic networks with specific structures.

[0037] The molar ratio of the transition metal inorganic salt to the amide compound is (3-6):1; wherein the molar ratio of the transition metal inorganic salt to the amide compound includes but is not limited to 3:1, 3.3:1, 4:1, 4.5:1, 5:1, 5.5:1, and 6:1. Within this molar ratio range, the ratio of the transition metal inorganic salt to the amide compound is more appropriate, which can provide a more suitable coordination environment and help form a stable metal organic network and a desired coordination structure, such as an elongated octahedral coordination unit.

[0038] The first solvent and the second solvent are the same or different, the first solvent includes but is not limited to ethanol and / or methanol, and the second solvent includes but is not limited to ethanol and / or methanol; the present application does not limit the types of the first solvent and the second solvent, as long as the boiling points of the first solvent and the second solvent are lower than the boiling points of the amide compounds, that is, the first solvent and the second solvent are both low boiling point solvents.

[0039] Step S103: After mixing the first reaction liquid and the second reaction liquid, perform a stirring reaction to obtain a mixed solution, wherein the stirring reaction is performed at room temperature, that is, the stirring temperature is 25° C., and the stirring time is 1.5-2.5 hours.

[0040] Step S104. Solid-liquid separation: Take the liquid component in the mixed solution in step S103, remove the first solvent and the second solvent in the liquid component, and obtain a metal organic network glass material; wherein the boiling points of the first solvent and the second solvent are lower than the boiling points of the amide compound.

[0041] The first solvent and the second solvent in the liquid component can be removed by rotary evaporation. The temperature of the rotary evaporation is 70-80° C. The time of the rotary evaporation can be determined according to the specific situation as long as there are no more bubbles in the solution.

[0042] This application synthesizes elongated octahedral coordination units by using the synergistic effect of amide ligands and anionic ligands, and introduces hydrogen bonds and weak electrostatic interactions between spatially separated cations and anions between these coordination units, so that the obtained metal organic network glassy material has a lower melting point than other metal organic network glassy materials, which is only about 100°C. The main reason for this property is that charge delocalization and spatial separation of anions and cations reduce the electrostatic attraction between charges, as well as the synergistic effect of strong and weak ligands and weak hydrogen bond interactions. At the same time, a short-range ordered and long-range disordered glassy structure is formed, which gives the material a series of physical and chemical properties, allowing it to be used in optical materials and energy storage materials.

[0043] The main reason why metal organic network glassy materials are easy to thermally decompose is that the decomposition temperature of the ligand is lower than its melting point. At present, most of them are prepared by melting method, which means that the raw material liquid will be partially decomposed before the ligand is completely melted. The present application can greatly reduce the temperature required for its preparation by solution method preparation, so it can effectively reduce thermal decomposition. Cold crystallization is due to the formation of a small amount of crystal nucleus clusters during the cooling process, and then the crystal nucleus clusters mature, grow and crystallize during the reheating process. The metal organic network glassy material provided by the present application has a strong glass forming ability due to the synergistic effect of its coordination bond and hydrogen bond, so that the formation of crystal nuclei during the cooling process can be avoided, so cold crystallization can be avoided.

[0044] Method 2: Melting method

[0045] Step S201: Heat the amide compound to obtain a molten amide compound.

[0046] The amide compounds in this step are the same as those in the solution method. If the amide compounds selected are liquid at room temperature, they can react at room temperature. The molten state here refers to the state after the solid-liquid phase transition, but not yet in the boiling state. For example: water is solid below 0°C, liquid above 0°C, that is, molten state, and boiling above 100°C, that is, the molten state here is between 0-100°C.

[0047] If the amide compound selected is solid at room temperature, it only needs to be heated to 5-10℃ above its melting point; however, for amide compounds with a melting point below 0℃, such as the above-mentioned N,N-dimethylformamide which is -63℃, it is no longer necessary to heat to 5-10℃ above its melting point for reaction, because its reaction activity must be taken into consideration at this time, so it can generally be reacted directly at room temperature 25℃.

[0048] Step S202. Stirring the transition metal inorganic salt and the molten amide compound for reaction, wherein the stirring reaction temperature is not lower than the temperature of the molten amide compound and is not higher than the boiling point or decomposition temperature of the molten amide compound. In the present application, the stirring reaction temperature can be 105-110° C., and the stirring reaction time is 1.5-2.5 hours.

[0049] Heating the amide compound to a molten state helps to improve its solubility, making it easier to fully mix with the transition metal inorganic salt. In the stirring reaction, making the temperature not lower than the temperature of the molten amide compound helps to maintain the uniformity of the reaction system and promote better mixing of the reactants. It also helps to increase the reaction rate. Within this temperature range, the reaction rate may be higher, which helps to form a metal organic network in a shorter time. At the same time, making the temperature of the stirring reaction not higher than the boiling point or decomposition temperature of the molten amide compound is to avoid excessive decomposition. Too high a temperature may lead to an irreversible decomposition reaction, thereby affecting the formation of the metal organic network. And the appropriate temperature range helps to maintain the coordination environment, so that the transition metal inorganic salt and the amide compound can form a metal organic network structure under suitable conditions.

[0050] Step S203: Allow the mixture obtained in step S202 to cool naturally to room temperature to obtain the metal organic network glass material.

[0051] The solution method is suitable for large-scale preparation, but it is inevitable that a small amount of solvent molecules will remain in the preparation process. Preparation by the melt method can make the molecular structure of the product clearer, and there is no interference from solvent molecules, so the prepared sample is more suitable for analyzing the molecular structure. Moreover, the ligand selected in this application has a low melting point, so it can be prepared by the melt method. In theory, each metal organic network glass material has an equilibrium melting temperature T mHowever, in reality, the decomposition temperature T of many compounds is dec Therefore, the main challenge in the synthesis of coordination network-forming liquids is to design the T m <T dec So far, the research on the melting transition of 2D and 3D metal-organic network glassy materials has mainly focused on improving T by using ligands with high thermal stability such as imidazole. dec , while the design has an inherently lower T m The compounds of are relatively less concerned. This application establishes a general thermodynamic strategy to reduce the melting temperature of three-dimensional metal-organic networks by utilizing a series of stable amide compounds.

[0052] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0053] Example 1

[0054] This embodiment provides a metal organic network glassy material, and the preparation method thereof comprises the following steps:

[0055] (1) At a temperature of 25° C., 1.26 g of anhydrous manganese chloride was dissolved in 30 mL of ethanol to prepare a manganese chloride ethanol solution.

[0056] (2) 2.96 g of methyl urea was dissolved in 20 mL of ethanol at 25° C. to prepare a methyl urea ethanol solution.

[0057] (3) The manganese chloride ethanol solution and the methyl urea ethanol solution are fully mixed and stirred for 2 hours to obtain an organic metal complex ethanol solution.

[0058] (4) The above metal organic complex ethanol solution is filtered through filter paper with a pore size of 0.22 μm to obtain a filtrate.

[0059] (5) The filtrate is evaporated at 70° C. to remove the solvent to obtain a viscous metal organic complex, and then the viscous material is cooled to room temperature to obtain the metal organic network glass material.

[0060] Example 2

[0061] This embodiment provides a metal organic network glassy material, and the preparation method thereof comprises the following steps:

[0062] (1) At a temperature of 25°C, weigh 2.96 g of methyl urea and heat it to 110°C to melt it into a liquid state.

[0063] (2) At a temperature of 25°C, 1.26 g of anhydrous manganese chloride was weighed and added to melted methyl urea.

[0064] (3) At 110° C., the anhydrous manganese chloride and methyl urea are fully mixed and stirred for 2 hours to form a molten material.

[0065] (4) Naturally cooling the molten material to room temperature to obtain the metal organic network glass material.

[0066] Example 3

[0067] This embodiment provides a metal organic network glassy material, and the preparation method thereof comprises the following steps:

[0068] (1) At a temperature of 25° C., 1.3 g of anhydrous cobalt chloride was dissolved in 30 mL of ethanol to prepare a cobalt chloride ethanol solution.

[0069] (2) 2.96 g of methyl urea was dissolved in 20 mL of ethanol at 25° C. to prepare a methyl urea ethanol solution.

[0070] (3) The cobalt chloride ethanol solution and the methyl urea ethanol solution are fully mixed and stirred for 2 hours to obtain an organic metal complex ethanol solution.

[0071] (4) The above metal organic complex ethanol solution is filtered through filter paper with a pore size of 0.22 μm to obtain a filtrate.

[0072] (5) The filtrate is evaporated at 70° C. to remove the solvent to obtain a viscous metal organic complex, and then the viscous material is cooled to room temperature to obtain the metal organic network glass material.

[0073] Example 4

[0074] This embodiment provides a metal organic network glassy material, and the preparation method thereof comprises the following steps:

[0075] (1) At a temperature of 25°C, weigh 2.96 g of methyl urea and heat it to 110°C to melt it into a liquid state.

[0076] (2) At a temperature of 25°C, 1.3 g of anhydrous cobalt chloride was weighed and added to melted methyl urea.

[0077] (3) At 110° C., the anhydrous cobalt chloride and methyl urea are fully mixed and stirred for 2 h to form a molten material.

[0078] (4) Naturally cooling the molten material to room temperature to obtain the metal organic network glass material.

[0079] Example 5

[0080] This embodiment provides a metal organic network glassy material, and the preparation method thereof comprises the following steps:

[0081] (1) At 25°C, 1.3 g of anhydrous nickel chloride was dissolved in 30 mL of ethanol to prepare a cobalt chloride ethanol solution.

[0082] (2) 2.96 g of methyl urea was dissolved in 20 mL of ethanol at 25° C. to prepare a methyl urea ethanol solution.

[0083] (3) The nickel chloride ethanol solution and the methyl urea ethanol solution are fully mixed and stirred for 2 hours to obtain an organic metal complex ethanol solution.

[0084] (4) The above metal organic complex ethanol solution is filtered through filter paper with a pore size of 0.22 μm to obtain a filtrate.

[0085] (5) The filtrate is evaporated at 70° C. to remove the solvent to obtain a viscous metal organic complex, and then the viscous material is cooled to room temperature to obtain the metal organic network glass material.

[0086] Example 6

[0087] This embodiment provides a metal organic network glassy material, and the preparation method thereof comprises the following steps:

[0088] (1) At a temperature of 25°C, weigh 2.96 g of methyl urea and heat it to 110°C to melt it into a liquid state.

[0089] (2) At a temperature of 25°C, 1.3 g of anhydrous nickel chloride was weighed and added to melted methyl urea.

[0090] (3) At 110° C., the anhydrous nickel chloride and methyl urea are fully mixed and stirred for 2 h to form a molten material.

[0091] (4) Naturally cooling the molten material to room temperature to obtain the metal organic network glass material.

[0092] Example 7

[0093] This embodiment is substantially the same as embodiment 1, except that the amount of methyl urea added is 5.18 g.

[0094] The final product obtained in this embodiment is a crystalline substance rather than a metal organic network glassy material.

[0095] Test Example 1

[0096] This experimental example performs structural characterization on the metal organic network glassy material provided in Example 1. The present application utilizes extended X-ray absorption fine structure (EXAFS) to quantitatively determine the coordination number and distance of manganese, referring to the first shell energy information of the K-edge energy spectrum. Figure 1 The real and imaginary parts of the Mn-O coordination EXAFS spectrum are shown. After characterization and theoretical fitting, the fitting results show that the coordination number of Mn-O in the metal organic network glassy material is 4.0, and its coordination distance is The coordination number of Mn-Cl is 1.4(9), and its coordination distance is To further reveal this coordination structure, X-ray absorption near edge structure (XANES) was then used to analyze its manganese K edge, with reference to manganese oxide and potassium permanganate standard manganese compounds; the results are as follows Figure 2 As shown, unlike the strong edge pre-peak of the tetrahedral potassium permanganate with low symmetry, the Mn-O coordination in the metal organic network glassy material has no edge pre-peak, similar to the octahedral manganese oxide with high symmetry. This is because in the octahedron with high symmetry, the electronic transition from 1s to 3d orbit is dipole-forbidden, while in the tetrahedron with low symmetry (such as potassium permanganate), this transition is dipole-allowed due to the dp hybrid orbit. The above test results clearly illustrate the Mn-O coordination structure in the metal organic network glassy material provided in Example 1 of the present application, including 1 Mn ion and 4 methyl ureas, and 2 longer Mn-Cl bonds, presenting an elongated octahedral configuration. Longer and weaker Mn-Cl donor bonds are often easily destroyed by other stronger field ligands. This asymmetric interaction in MM also makes the degree of freedom larger, increases the disorder of the structure, and ultimately improves the glass forming ability of MM.

[0097] from Figure 1 and 2 It can be seen that the metal organic network glassy material provided in Example 1 of the present application is formed based on the strong and weak ligand matching mechanism of amide ligands and anionic ligands, forming elongated octahedral coordination units, and these coordination units are interconnected by hydrogen bonds and weak electrostatic interactions between spatially separated cations and anions.

[0098] Test Example 2

[0099] This test example measures the properties of the metal organic network glassy materials provided in Examples 1-6, including specific heat and glass transition temperature. The specific heat and glass transition temperature are measured by differential scanning calorimetry (DSC), and the test steps are as follows:

[0100] 1. Equipment preparation: Differential scanning calorimetry (DSC) measurements were performed using a Mettler Toledo TGA / DSC1 instrument, and the experiments were performed in a nitrogen-protected environment.

[0101] 2. Sample preparation: Take about 5 mg of sample and put it into a standard 40 μL aluminum crucible. Control setting: Use an empty aluminum crucible as a reference sample.

[0102] 3. Heating process: Heat the sample from -20°C and increase the temperature to 130°C at a rate of 5°C per minute.

[0103] 4. Cooling process: Starting from 130°C, cool the sample to -20°C at the same speed (5°C per minute).

[0104] 5. Specific heat calculation: Compare the DSC curve of the sample with the DSC curve of a known reference material (such as sapphire) to calculate the specific heat capacity of the sample.

[0105] 6. Determination of glass transition temperature: Observe the change point of heat flow on the DSC curve to determine the glass transition temperature (Tg), which is the temperature value corresponding to the change point of the curve.

[0106] The measurement results of the above items are shown in Table 1. The thermodynamic properties of the metal organic network glassy material provided in Example 1 are shown in Table 1. Figure 2 The crystallographic diffraction pattern is shown in Figure 3 As shown in the figure, the rheological properties are Figure 4 shown.

[0107] Table 1

[0108] Group Specific heat (J / gK) Glass transition temperature(℃) Example 1 2.12 10 Example 2 2.15 16 Example 3 2.11 5 Example 4 2.13 12 Example 5 2.16 4 Example 6 2.13 9

[0109] As can be seen from Table 1, the specific heat of the samples prepared by the solution method is basically the same, but the glass transition temperature of the samples prepared by the solution method is significantly lower than that prepared by the melting method. This is because the solution method will inevitably leave some solvent molecules in the material, the viscosity will be slightly reduced, the binding force between molecules will be reduced accordingly, and the glass transition temperature will also be reduced; however, the solution method is more suitable for large-scale preparation. At the same time, as the atomic number of the metal increases, its corresponding glass transition temperature tends to decrease.

[0110] Figure 3 The X-ray diffraction (XRD) pattern of the metal organic network glassy material of Example 1 of the present application is compared with the crystal structures of methyl urea and manganese chloride. Its characteristic of having no diffraction peak proves that it is an amorphous glassy structure.

[0111] Figure 4 The differential scanning calorimetry (DSC) curves of the metal organic network glassy material of Example 1 of the present application and the crystalline material formed after being fully ground, and the results show the glass transition temperature (T g) is about 10℃. The cooling trace further confirms that its cooling process follows an amorphization process rather than a crystallization process. Its crystalline material will melt during the heating process, and its melting point (T m ) is 102.8°C. Glass-forming ability is usually measured by T g / T m Here, the material’s T g / T m It is about 0.75, which is significantly larger than 2 / 3 according to Kauzmann's law, reflecting the high GFA and high anti-crystallization ability of the metal organic network glassy material.

[0112] Figure 5 The viscosity of the metal organic network glassy material at different temperatures is fitted by the MYEGA equation, and the viscosity of the metal organic network glassy material at different temperatures is calculated by using T g As a reduced parameter, its brittleness index is 64, which belongs to the medium region and has a certain glass-forming ability, but it is obviously deviated from the Arrhenius behavior of SiO2 glass (m=20). This is because metal organic network glassy materials are coordination bond and hydrogen bond system glasses, while SiO2 is a typical covalent bond glass.

[0113] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

Claims

1. A metal organic network glassy material, characterized in that: It includes a transition metal inorganic salt and an amide compound, wherein the amide compound serves as a ligand; The molar ratio of the transition metal inorganic salt to the amide compound is (3-6):

1.

2. The metal organic network glassy material according to claim 1, characterized in that: The cations in the transition metal inorganic salt include Mn 2+ , Fe 2+ 、Co 2+ 、Ni 2+ , Cu 2+ and Zn 2+ At least one of; the anion in the transition metal inorganic salt includes Cl - 、NO3 - and SO4 2- At least one of; Optionally, the amide compound includes at least one of acetamide, isobutylamide, oxalyl diamide, N,N-dimethylformamide, dimethylacetamide, succinamide, carbonamide, N-methyl urea and 1,3-bis(hydroxymethyl)urea.

3. The metal organic network glassy material according to claim 2, characterized in that: The transition metal inorganic salt is anhydrous manganese chloride, and the amide compound is methyl urea; Or, the transition metal inorganic salt is anhydrous cobalt chloride, and the amide compound is methyl urea; Alternatively, the transition metal inorganic salt is anhydrous nickel chloride, and the amide compound is methyl urea.

4. A method for preparing a metal organic network glassy material as claimed in any one of claims 1 to 3, characterized in that: include: Mixing the transition metal inorganic salt with a first solvent to obtain a first reaction solution; mixing the amide compound with a second solvent to obtain a second reaction solution; The first reaction liquid and the second reaction liquid are mixed and stirred to react to obtain a mixed solution; a liquid component in the mixed solution is separated by solid-liquid separation, and the first solvent and the second solvent in the liquid component are removed to obtain the metal organic network glass material; The boiling points of the first solvent and the second solvent are lower than the boiling point of the amide compound.

5. The preparation method according to claim 4, characterized in that: The first solvent and the second solvent are the same or different; The first solvent includes ethanol and / or methanol, and the second solvent includes ethanol and / or methanol.

6. The preparation method according to claim 5, characterized in that: 20-30 mL of the first solvent is added to every 1 mmoL of the transition metal inorganic salt.

7. The preparation method according to any one of claims 4 to 6, characterized in that: 4-6 mL of the second solvent is added to every 1 mmol of the amide compound.

8. The preparation method according to any one of claims 4 to 6, characterized in that: The stirring temperature is 25° C., and the stirring time is 1.5-2.5 h.

9. A method for preparing the metal organic network glassy material according to any one of claims 1 to 3, characterized in that: include: heating the amide compound to obtain a molten amide compound; Stirring the transition metal inorganic salt and the molten amide compound to react, and cooling to obtain the metal organic network glassy material; The temperature of the stirring reaction is not lower than the temperature of the molten amide compound, and is not higher than the boiling point or decomposition temperature of the molten amide compound.

10. The preparation method according to claim 9, characterized in that: The temperature of the stirring reaction is 105-110° C., and the time of the stirring reaction is 1.5-2.5 h.